(untitled) (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
his research is motivated by the rampant phenomenon of catcalling in Indonesia which is a form of verbal sexual harassment but is often considered as common by the community. Although Indonesia already has a legal umbrella through Article 281 paragraph (2) of the Criminal Code and Article 5 of Law No. 12 of 2022 concerning the Crime of Sexual Violence (TPKS Law), data shows that there is still a high dark number of crimes where 89.5% of victims choose not to report due to distrust of the authorities and the assumption that the incident is a personal matter. The purpose of this study is to analyze the victim’s view on the regulation and protection of catcalling victims in Indonesia and to evaluate the effectiveness of criminalizing the perpetrators. Using empirical legal research methods through conceptual and legislative approaches, this study collects primary data through surveys and secondary data through literature studies. The results of the study show that the victimology perspective highlights the failure of the legal system in providing adequate protection; The Criminal Code is considered too offender-centered, while the TPKS Law, which is thick with feminist jurisprudence nuances, has weaknesses in the aspect of due process of law due to the ease of proof which is considered less rational in the adjudication process. This research contribution provides an understanding of the urgency of improving legal policies that are balanced between the protection of victims’ rights and the principle of legal justice.